Pengaruh Promosi, Brand Image Dan Price Fairness Terhadap Keputusan Pembelian Momoyo - Vita Pidia Astuti; Mukhroji Mukhroji (JURNAL ILMIAH EKONOMI DAN MANAJEMEN, 2026)
Abstract. Rising rivalry within the food and beverage sector pushes firms to develop a sharper grasp of what drives consumers to buy. This study examines how promotion, brand image, and price fairness shape purchase decisions for Momoyo products in Bumiayu. A quantitative survey design was used, with questionnaires distributed to respondents who had previously bought Momoyo. Respondents were selected through purposive sampling, and the resulting data were processed using multiple linear regression in IBM SPSS Statistics. Findings show that promotion, taken on its own, does not significantly affect purchase decisions. Brand image, by contrast, exerts a positive and significant influence on purchase decisions and emerges as the strongest predictor among the three. Price fairness likewise contributes a positive and significant effect on purchase decisions.. Overall, the results suggest that reinforcing brand image and applying pricing that consumers perceive as fair are key levers for boosting purchase decisions, while current promotional efforts warrant further refinement to become more effective.Keywords: Promotion, Brand image, Price fairness, Purchasing Decision, Momoyo